Hajj Financing Models: Fiqh Analysis of Payment Contracts for Hajj Funds at the Ministry of Religious Affairs in Indonesia - Mulyono Jamal; Khurun'in Zahro'; Eko Nur Cahyo; Nuriwanda Azizah Nugraheni (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam)
Hajj is the perfecting of the pillars of Islam of a Muslim, the fifth pillar of Islam, and is carried out for those who are able. In Indonesia, the hajj is organized by the Ministry of Religious Affairs (MORA) in Jakarta and the regional offices of MORA throughout Indonesian provinces. To repay funds, prospective pilgrims do so at the bank receiving the BPS-BPIH hajj deposit. The contract used when registering prospective Pilgrims is a wakalah contract. However, when they come to the bank, the bank will ask them what contract will be applied, whether wadi'ah or murabahah. This research aims to disclose the Payment of Funds for prospective Hajj Pilgrims and analyze the principles of the contract applied in the repayment of funds for prospective pilgrims. The type of research used is field research with qualitative methods using descriptive analysis. The data sources in this study are primary and secondary data, then use descriptive data analysis as material for research findings. There are two findings in this study. The first is the agreement on the repayment of the Hajj Pilgrim Candidate Fund, which starts from the Wakalah contract between prospective Pilgrims with the Ministry of Religious Affairs, then the Wadi'ah and or Mudharabah Contract between prospective Hajj Pilgrims with BPS-BPIH, and the Ijarah Mausufah fi Dzimmah agreement between prospective Pilgrims represented by the Ministry of Religious Affairs and BPKH as the Hajj fund manager. Second, the fiqh analysis of the principle of the contract applied to the Repayment of The Hajj Pilgrim Candidate Fund is Wakalah and is appropriate as it should be, but what needs to be considered is the understanding of prospective Pilgrims for the contracts that have been applied.